DNA methylation landscape of tumor‐associated macrophages reveals pathways, transcription factors and prognostic value relevant to triple‐negative breast cancer patients. Issue 6 (9th December 2022) - Hey, Joschka; Halperin, Coral; Hartmann, Mark; Mayer, Shimrit; Schönung, Maximilian; Lipka, Daniel B.; Scherz‐Shouval, Ruth; Plass, Christoph
Abstract: The accumulation of myeloid cells, particularly tumor‐associated macrophages (TAMs), characterizes the tumor microenvironment (TME) of many solid cancers, including breast cancer. Compared to healthy tissue‐resident macrophages, TAMs acquire distinct transcriptomes and tumor‐promoting functions by largely unknown mechanisms. Here, we hypothesize the involvement of TME signaling and subsequent epigenetic reprogramming of TAMs. Using the 4T1 mouse model of triple‐negative breast cancer, we demonstrate that the presence of cancer cells significantly alters the DNA methylation landscape of macrophages and, to a lesser extent, bone marrow‐derived monocytes (BMDMs). TAM methylomes, dissected into BMDM‐originating and TAM‐specific epigenetic programs, implicated transcription factors (TFs) and signaling pathways involved in TAM reprogramming, correlated with cancer‐specific gene expression patterns. Utilizing published single‐cell gene expression data, we linked microenvironmentally‐derived signals to the cancer‐specific DNA methylation landscape of TAMs. These integrative analyses highlighted the role of altered cytokine production in the TME (eg, TGF‐β, IFN‐γ and CSF1) on the induction of specific TFs (eg, FOSL2, STAT1 and RUNX3) responsible for the epigenetic reprogramming of TAMs. DNA methylation deconvolution identified a TAM‐specific signature associated with the identified signaling pathways and TFs, corresponding with severe tumor grade and poor prognosis of breast cancer patients. Similarly, immunosuppressive TAM functions were identified, such as induction of the immune inhibitory receptor‐ligand PD‐L1 by DNA hypomethylation of Cd274 . Collectively, these results provide strong evidence that the epigenetic landscapes of macrophages and monocytes are perturbed by the presence of breast cancer, pointing to molecular mechanisms of TAM reprogramming, impacting patient outcomes. Abstract : What's new? In many solid cancers, tumor‐associated macrophages (TAMs) congregate in the microenvironment around the tumor. These TAMs have distinct gene expression profiles and help the tumor survive and grow. Here, the authors investigated the differences between TAMs from a mouse model of triple‐negative breast cancer and mammary gland macrophages as well as monocytes from healthy mice. They show for the first time that cancer cells alter DNA methylation patterns in macrophages. These alterations, they found, affected transcription factors and signaling pathways associated with breast cancer progression and prognosis.